Enhancing Brackish Water Desalination using Magnetic Flow-electrode Capacitive Deionization. (1st June 2022) - Xu, Longqian; Peng, Shuai; Mao, Yunfeng; Zong, Yang; Zhang, Xiaomeng; Wu, Deli
Highlights: A magnetic field-assisted FCDI system is proposed. Magnetic field increases the concentration of flow electrodes near the current collector. The formation of continuous electron transport network facilitates ion adsorption. Magnetic field enables a 78.9%–205% enhancement in the ASRR of FCDI. Electrode-water separation efficiency can be enhanced by magnetic field. Abstract: Flow-electrode capacitive deionization (FCDI) is viewed as a potential alternative to the current state-of-the-art electrodriven technology for the desalination of brackish water. However, the key shortcoming of the FCDI is still the discontinuous nature of the electrode conductive network, resulting in low electron transport efficiency and ion adsorption capacity. Here, a novel magnetic field-assisted FCDI system (termed magnetic FCDI) is proposed to enhance brackish water desalination, simply by using magnetic activated carbon (MAC) as flow electrodes. The results show that the assistance from the magnetic field enables a 78.9% – 205% enhancement in the average salt removal rate ( ASRR ) compared with that in the absence of a magnetic field, which benefits from the artificial manipulation of the flow electrode transport behavior. In long-term tests, the stable desalination performance of magnetic FCDI was also demonstrated with a stable ASRR of 0.70 μmol cm –2 min –1 and energy-normalized removed salt ( ENRS ) of 8.77 μmol J –1 . In addition, magnetic field also enables the regeneration of the electrode particles from the concentrated electrolyte. In summary, the findings indicate that the magnetic FCDI is an energy-efficient and operation convenient technology for brackish water desalination. Graphical abstract: Image, graphical abstract